Determination of hydrogen peroxide in some local pharmaceutical disinfectants by continuous flow injection analysis via turbidimetric (T180o) and scattered light effect at two opposite positions (2N90o ) using Ayah 4SW-3D-T180o -2N90o -Solar - CFI Analyse - Turkey Al-Awadie, Nagam S.; F. Khudhair, Ahmed (Iraqi Journal of Science, 2023)
An indirectly method is used to determine hydrogen peroxide. The method based on oxidation of chromium (III) ion by hydrogen peroxide in basic medium to form chromate ion which react with barium (II) ion to produce a yellow precipitate (BaCrO4). Under the optimum established conditions, the linear range of 0.50-25.00 mmol L-1 along with correlation coefficient (r) of 0.9992, Limit of detection (LOD) 0.68 μg / 100 μL, precision expressed as relative standard deviation for six replication measurements at 5.0 mmol.L-1 H2O2 of less than 2% were obtained for hydrogen peroxide. The developed method was successfully applied for the estimation of H2O2 in three pharmaceuticals preparation of different companies using continuous flow injection or stop-flow injection technique.